Exploring New Delhi Metallo Beta Lactamases in Klebsiella pneumoniae and Escherichia coli: genotypic vs. phenotypic insights - Noor Ul Ain; Linzy Elton; Zahra Sadouki; Timothy D. McHugh; Saba Riaz (Annals of Clinical Microbiology and Antimicrobials)
Abstract Background Carbapenemase-producing Enterobacterales pose a serious clinical threat, particularly in high-burden settings of carbapenem-resistant Escherichia coli and Klebsiella pneumoniae (CREK), where rapid detection tools are essential to aid patient management. In this study, we focused on bla NDM, the most frequently reported carbapenemase in the region, and evaluated a combined phenotypic (lateral flow) and genotypic (PCR and WGS) approach for its detection. This research underscores the utility of lateral flow assays as a practical alternative to resource-intensive genotypic methods, offering a scalable solution for settings with limited laboratory capacity. Method One hundred seventy-seven extensively drug-resistant strains were characterized using MALDI-TOF. Isolates were analyzed to detect Carbapenem-resistant Escherichia coli and Klebsiella pneumoniae (CREK) using disk diffusion, MIC test, and PCR targeting bla NDM. Antibiotic susceptibility patterns were analyzed and visualized using single-linkage hierarchical clustering, with results displayed on a permuted heat map. Immunochromatographic assay, RESIST-5 O.K.N.V.I (Coris Bioconcept®) was used for CREK isolates [(n = 17), positive and negative)] and Oxford Nanopore Sequencing was conducted on subsets [(n = 5) bla NDM-positive co-producers of bla NDM and bla OXA, and (n = 2) bla NDM-negative bla OXA producers) to evaluate the reliability of phenotypic and genotypic tests. Result Most of the XDR strains (90%) were CREK, with K. pneumoniae (71.2%) more prevalent than E. coli (28.7%) (p < 0.05). All CREK strains exhibited complete resistance (100%) to multiple antibiotics with 66% showing sensitivity to levofloxacin. Furthermore, K. pneumoniae (57.8%) had higher bla NDM gene prevalence than E. coli (36.9%). Among bla NDM-positive CREK, lateral flow assay revealed approximately half of each bacteria type co-produced bla OXA (E.coli, 52.9%), and (K. pneumoniae, 47%). For bla NDM-negative strains, bla OXA was more prevalent in K. pneumoniae (82.35%) than E. coli (41%) (p < 0.05). Comparing phenotypic to genotypic assays, E. coli showed 100% (CI 80.49 − 100%) sensitivity and specificity with a high Kappa agreement coefficient (0.91) (CI 95% 0.661–1, p < 0.01), whereas K. pneumoniae assays had lower sensitivity and specificity (40%) (CI 5.27 − 85.34%), with a lower Kappa agreement coefficient (0.20) (CI 95% 0.104–0.298, p < 0.01). Conclusion This study demonstrates the value of the RESIST-5 O.K.N.V.I. lateral flow assay as a rapid and reliable diagnostic tool for detecting bla NDM in Escherichia coli, with strong agreement to PCR and WGS. While performance for Klebsiella pneumoniae was lower, the assay offers a practical alternative in resource-limited settings, aiding antimicrobial stewardship and improving diagnostic capacities in high-burden regions.